Efficacy of a mineralized collagen bone-grafting material for peri-implant bone defect reconstruction in mini pigs. Issue 2 (21st March 2019) - Wang, Enbo; Han, Jianmin; Zhang, Xuehui; Wu, Yuhan; Deng, Xu-Liang
Abstract: The mechanism of the mineralization process induced by natural mineralized collagen (MC) has been investigated for decades. The purpose of this study was to investigate the efficacy of self-assembled MC for peri-implant bone defect reconstruction in a mini pig. A standardized peri-implant bone defect model was created using 14 mini pig mandibles. Two materials were evaluated, i.e. a mixture of hydroxyapatite and collagen (Type A, TA), and self-assembled MC (Type B, TB). Bio-Oss (BO) and untreated (blank control, BC) groups were used as controls. After 3- and 6-month healing periods, the mini pigs were sacrificed for histomorphometric and microcomputed tomography analysis. After 3 months of healing, the average alveolar ridge height was 3.27 ± 1.57 mm for group TA, 3.28 ± 2.02 mm for group TB and 3.37 ± 1.09 mm for group BO, while group BC showed the lowest height of 2.68 ± 0.47 mm. After 6 months of healing, the average alveolar ridge height was 2.64 ± 1.13 mm for group TA, 4.31 ± 1.80 mm for group TB and 3.87 ± 1.38 mm for group BO, while group BC showed the lowest height of 2.48 ± 1.80 mm. The experimental groups and control group showed similar bone volume density, bone complexity and histological reaction. The self-assembled MC (Type B) stimulated new bone formation in the reconstruction of deficient alveolar ridges around the dental implant; it also displayed excellent clinical operability compared with bone grafts without collagen.